(untitled) (Journal of Parents and Teachers, 2014)
With the aim of successfully tackling the new course, the following article proposes a timetable as the key to organisation. It offers keys about what characteristics this timetable should have, such as personal, realistic, flexible, etc. In addition, one of the benefits of creating a timetable is to encourage a study habit in yourself. If you want to know how to make your schedule we invite you to read the article.